Analysis of Remote Displacement Patterns Monitored by Tiltmeters During Fluid Injection Into Reservoirs - Deng, Zhigang; Li, Hong; Wang, Longjiang; Liu, HongZhi; Wang, Zhenwei (Frontiers in Earth Science, 2019)
In order to take far-field translational tilts into account during studying reservoir flow process of CO2 injection, a group of tiltmeters were installed as array covering estimate range of ground spreading from the injection well. The measurements were applicable to ground deformations during a fracturing stimulation treatment, a short-term test of CO2 injection into relatively shallow coal seams and a CO2 injection into deep saline aquifer. An attempt to quantitatively model the rational association between reservoir volumetric disturbance underground and its induced corresponding rather slight distortion on surface was presented. It is as well demonstrated how to sufficiently manipulate vertical unstructured and horizontal divergent model numerical discretization, which eventually makes it feasible to study mechanism between reservoir flow and reservoir Geomechanics by full-field reservoir model. The potential algorithms to improve the computational efficiency and an actual demand for an ambitious solver to inverse coupling problem are finally discussed. The study proposed the development of high-efficiency software package fully capable of dealing with reservoir flow and reservoir Geomechanics so as to implement the history match study not only on a reservoir itself being injected but also including the full field deformation performance up to the costly ground displacement monitoring data.